Taxing Africa Coercion, Reform and Development - Moore, Mick (African Arguments, 2018)
Taxation has been seen as the domain of charisma-free accountants, lawyers and number crunchers - an unlikely place to encounter big societal questions about democracy, equity or good governance. Yet it is exactly these issues that pervade conversations about taxation among policymakers, tax collectors, civil society activists, journalists and foreign aid donors in Africa today. Tax has become viewed as central to African development. Written by leading international experts, Taxing Africa offers a cutting-edge analysis on all aspects of the continent's tax regime, displaying the crucial role such arrangements have on attempts to create social justice and push economic advancement. From tax evasion by multinational corporations and African elites to how ordinary people navigate complex webs of 'informal' local taxation, the book examines the potential for reform, and how space might be created for enabling locally-led strategies. The eBook editions of this book are available open access under a CC BY-NC 3.0 licence on bloomsburycollections.com.